Comparative Study of Thematic Choice and Progression on Text Written by Humans and AI Machine - Suharsono, Suharsono; Ashadi, Ashadi; Sudartinah, Titik (Journal of Language and Literature, 2024)
The development of AI technology has enabled machines to carry out tasks that previously could only be done by humans. Scientists of AI have recently launched a tool called ChatGPT. It is a tool that can do whatever is ordered by humans, including making academic writing like an abstract. Thus, this study aimed to compare thematic choice and thematic progression on the text of research abstracts of undergraduate students of Teacher College and those by ChatGPT (AI machine). To analyze the data, this study employed the thematic structure of Systemic Functional Linguistics developed by Halliday Matthiessen and thematic progression developed by Bloor Bloor. The thematic choice was analyzed by observing the variety of themes appearing in the two texts, as well as the level of complexity and diversity used. Thematic progression was evaluated by examining how the themes are arranged and developed along with the development of the texts. The results of this study show that AI machine has reached a level of proficiency allowing AI to rival humans. Even though there are fundamental differences in thematic progression patterns between texts written by undergraduate students and ChatGPT, this study concludes that the two are not significantly different. Therefore, the researchers suggest that further research in a similar field may explore issues such as quality, creativity, and originality. Afterwards, this study also suggests that English teachers use this thematic structuring knowledge and skills to improve students’ writing skill. This study provides valuable insight into the capabilities and limitations of AI machine in imitating the human creative process of writing.